39.1k views
2 votes
Value of x (2x+43) (2x-3)

User Tangens
by
7.1k points

2 Answers

4 votes
The answer to this problem is -46!
Hope this helps
User MBielski
by
7.8k points
6 votes

Answer:

-46

Explanation:

2x+43=2x-3

We simplify the equation to the form, which is simple to understand

2x+43=2x-3

We move all terms containing x to the left and all other terms to the right.

+2x-2x=-3-43

We simplify left and right side of the equation.

0x=-46

0=-46

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

User Edward Comeau
by
7.7k points